Incorporação de resíduo cerâmico a um solo argiloso superficial de Manaus visando seu emprego em pavimentos - (:unkn) unknown (Universidade Federal do Amazonas, 2012)
The study in question presents an alternative to improve the technical characteristics of the clay soil representative of the city of Manaus, the addition of waste from the production of ceramic bricks, from the potteries of Iranduba - Amazonas. Therefore we performed: a) characterization of natural soil and crushed ceramic waste, encompassing particle size analysis, Atterberg limits, density of solids compaction test and b) soil mineralogical characterization of natural and ceramic waste through analysis by diffraction x-ray (XRD), and c) evaluate the mechanical behavior of natural soil sample and soil-aggregate mixture through the trials Simple compressive Strength (RCS) module and Resilience (MR). The results regarding the soil-residue mixture showed that (a) the larger the particle size the greater the residue compressive strength of the mixture, (b) the addition of industrial byproduct tends to soil generally, to reduce the modulus of resilience of mixture, (c) the soilceramic waste showed satisfactory results regarding the mechanical performance, allusive to natural soil, (d) considering the large amount of waste generated currently in production of ceramic bricks, one can conclude that this residue has potential as aggregate alternative in improving soils with low bearing capacity.
Keywords: Módulo de resiliência; Pavimento; Resíduo cerâmico; Ensaio de Compressão simples; Resilience; Pavement; Ceramic waste; Simple compression test; ENGENHARIAS